Pengaruh Literasi Keuangan, Sikap Keuangan, dan Pendapatan terhadap Perilaku Pengelolaan Keuangan UMKM di Kecamatan Banjaran Kabupaten Bandung - Via Septiani; Salza Adzri Arismutia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The MSMEs in Banjaran District, Bandung Regency have experienced notable growth; however, the quality of their financial management has not yet reached an optimal level. Effective financial management is essential to ensure business continuity and support decision-making processes. This study aims to analyze the impact of Financial Literacy, Financial Attitudes, and Income on the Financial Management Behavior of MSMEs in the same district. A quantitative approach with descriptive and verification methods was employed. Data were collected through questionnaires distributed to 93 respondents, selected from a total population of 1,262 MSMEs using the Slovin formula. The analysis results show an F value of 50.310, which exceeds the F table value of 2.611, leading to the acceptance of H4 and the rejection of H0. These results confirm that Financial Literacy, Financial Attitudes, and Income collectively have a significant effect on the Financial Management Behavior of MSMEs.